PENERAPAN PEMBELAJARAN KOOPERATIF METODE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR TEMBAKAN BEBAS (FREE THROW) PADA SISWA KELAS X-5 SISWA SMA KRISTEN PETRA 3 SURABAYA - Surjadi Hendra; Anung Priambodo (Arena, 2010)
Physical education, sport and health is one of the subjects that are given to students. One of the sports games that are in these subjects is basketball. One of the basic techniques of basketball should have shot the student is free (throw free). Teachers teaching in applying free shot (free throw) difficulties and obstacles and barriers due to lack of knowledge of students in basic techniques of basketball games especially the basic technique of free throw. During this learning model that is used more reference to